Yield Response to Nitrogen Management in a Corn-Soybean Sequence in North Central Kansas - A. A. Correndo; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2021)
The aim of this study was to evaluate the response of corn (Zea mays L.) grain yield to nitrogen (N) fertilizer application and its residual effect on soybean (Glycine max(L.) Merr.) seed yield. During the 2020 growing season, a corn-soybean rotation study was continued at Scandia, KS (USA), evaluating five N fertilizer rates in corn under both dryland and irrigated conditions. Average corn grain yields ranged from 110 to 206 bu/a for dryland, and from 198 to 221 bu/a for irrigated conditions. Under dryland, maximum corn yields were achieved with an apparent soil N supply level of 350 lb N/a (fertilizer N plus soil N); while removing the water limitations with irrigation resulted in corn grain yields maximized with ca. 250 lb N/a. Average soybean seed yields varied from 66 to 72 bu/a for dryland and from 72 to 79 bu/a for irrigated conditions. A lack of significant residual effect from previous corn N management was observed on soybean yields.
Keywords: yield response; maize; soybean; productivity; corn; nitrogen